Nicht-Holonome Liesche Differenzierung und lineare Zusammenhänge im Stützelemenlenraum - Bliznikas, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Близникас, Неголономное дифференцирование Ли и линейные связности в пространстве опорных элементовV. Bliznikas, Neholonominis Li diferenciavimas ir tiesiniai sąryšiai atraminių elementų erdvėje